Designing an automated control system for changing NPU energy release compensating for arising internal disturbing factors based on their approximation model - Brunetkin, Olexander; Beglov, Konstantin; Maksymov, Maksym; Baskakov, Volodymyr; Vataman, Viktoriia; Kryvda, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2022)
The necessity of keeping in working condition the sources of traditional electricity generation for dispatching the supply of electricity from the capacities of "green" electricity generation has been realized. Potentially, one of these sources may be nuclear power plants. An obstacle to their use as a participant in dispatching is the impossibility of maneuvering with power in a wide range. One of the reasons for limiting the range is the complexity of automatic compensation for the reactivity of the xenon oscillation reactor. Existing physical and mathematical models for calculating the parameters of processes in the reactor due to changes in its power because of its complexity cannot be used in operational automatic control systems. The task of constructing an approximation linear model of processes in the reactor in the form of a transfer function is set. To build an approximation model, the inverse problem is solved. The desired model is based on the condition of coincidence at some time interval of the results of solving it with the results of a detailed physical-mathematical model. To this end, a number of sequential actions are performed, including approximation of the results of the expanded physical-mathematical model using a series, the application of the Laplace transformation to this series, as well as Pade approximation obtained in the space of the images of the series. The method of control was proposed and an automatic control system (ACS) for energy production of nuclear power plant has been synthesized. To this end, the management system was integrated with the approximation model of the active zone, which provided the possibility for adjusting the quantitative degree of stability of the active zone. ACS consists of three control circuits. Such a structure has made it possible to compensate for the xenon oscillations that occur. Additionally, ACS reduces the movement of adjusting rods in the active zone, which reduces local power surges in nuclear fuel and leads to an increase in its durability